IDEOLOGI KAPITALISME DALAM NOVEL PAMELA KARYA SAMUEL RICHARDSON (Ideology of Capitalism in “Pamela” Novel by Samuel Richardson) - Ratnawati Ratnawati (Balai Bahasa Sulawesi Selatan, 2014)
This article is a kind of language analysis on literary works. Discourse of “Pamela” Novel is analyzed by usingCritical Discourse Analysis referring to Sara Mills and Norman Fairclough models. The result of the researchshows that subject of storytelling is Pamela as representation of proletariat class by placing the figure of Mr.B as a subordinate of Pamela while eliminating the authority of the bourgeois class. Description of languageis viewed in terms of type of word, antonym, and sentence form used. Interpretation of ideology of capitalismin this novel is viewed from reader’s community,and author background, and his social life. Explanation ofworkers exploitation by the bourgeoisand the proletariat classes struggle in terms of the values of honesty andkindness, increasing trust in God, as well as strengthening the family institution.